Overexpression of corticotropin-releasing factor in the nucleus accumbens enhances the reinforcing effects of nicotine in intact female versus male and ovariectomized female rats - Uribe, Kevin P. (Neuropsychopharmacology, 2019)
This study assessed the role of stress systems in the nucleus accumbens (NAc) in promoting sex differences in the reinforcing effects of nicotine. Intravenous self-administration (IVSA) of various doses of nicotine was compared following overexpression of corticotropin-releasing factor (CRF) in the NAc of female and male rats. Ovariectomized (OVX) females were also included to assess the role of ovarian hormones in promoting nicotine reinforcement. Rats received intra-NAc administration of an adeno-associated vector that overexpressed CRF (AAV2/5-CRF) or green fluorescent protein (AAV2/5-GFP). All rats were then given extended access (23 h/day) to an inactive and an active lever that delivered nicotine. Separate groups of rats received intra-NAc AAV2/5-CRF and saline IVSA. Rats were also allowed to nose-poke for food and water during IVSA testing. At the end of the study, the NAc was dissected and rt-qPCR methods were used to estimate CRF overexpression and changes in CRF receptors (CRFr1, CRFr2) and the CRF receptor internalizing protein, β-arrestin2 (Arrb2). Overexpression of CRF in the NAc increased nicotine IVSA to a larger extent in intact female versus male and OVX females. Food intake was increased to a larger extent in intact and OVX females as compared to males. The increase in CRF gene expression was similar across all groups; however, in females, overexpression of CRF resulted in a larger increase in CRFr1 and CRFr2 relative to males. In males, overexpression of CRF produced a larger increase in Arrb2 than females, suggesting greater CRF receptor internalization. Our results suggest that stress systems in the NAc promote the reinforcing effectiveness of nicotine in female rats in an ovarian hormone-dependent manner.